Rhabdomyolysis in a patient taking nebivolol - Ye Jin Kim; Hae Ri Kim; Hong Jae Jeon; Hyun Jun Ju; Sarah Chung; Dae Eun Choi; Kang Wook Lee; Ki Ryang Na (The Korean Society of Nephrology, 2016)
β Blockers such as propranolol and labetalol are known to induce toxic myopathy because of their partial β2 adrenoceptor agonistic effect. Nebivolol has the highest β1 receptor affinity among β blockers, and it has never been reported to induce rhabdomyolysis until now. We report a patient who developed rhabdomyolysis after changing medication to nebivolol. A 75-year-old woman was admitted to our hospital because of generalized weakness originating 2 weeks before visiting. Approximately 1 month before her admission, her medication was changed from carvedilol 12.5 mg to nebivolol 5 mg. Over this time span, she had no other lifestyle changes causing rhabdomyolysis. Her blood chemistry and whole body bone scan indicated rhabdomyolysis. We considered newly prescribed nebivolol as a causal agent. She was prescribed carvedilol 12.5 mg, which she was previously taking, instead of nebivolol. She was treated by hydration and urine alkalization. She had fully recovered and was discharged.